Looking south on the Pay Streak, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of photograph: Looking south or down the Pay Streak. Igorrote Village with thatched roofs in left center. Acme Tea Parlor and Igorrote village at left. PH Coll 727.641 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number